AB0611 Disease activity and organ damage in patient with childhood-onset systemic lupus erythematosus, from childhood to adulthood: a retrospective study over the last 25 years. (12th June 2018) - Hosticka, E.; Novoselec, M.; Sestan, M.; Cekada, N.; Frkovic, M.; Padjen, I.; Sentic, M.; Anic, B.; Jelusic, M.
Abstract : Background: Although clinical symptoms and immunological findings are common in both children and adults with systemic lupus erythematosus (SLE), children generally have a more severe clinical presentation at the time of diagnosis with a larger number of affected organs, a much more aggressive clinical course and greater chance of developing organ damage over time. Objectives: To compare the SLEDAI-2K disease activity index in patients with SLE at the time of diagnosis with SLEDAI-2K in the same patients in adulthood and to compare of the SLICC/ACR damage index (SDI) in patients with cSLE at the last follow up in childhood with SLICC/ACR of the same patients in adulthood. Methods: This retrospective study included children who were diagnosed with cSLE, according to the ACR 1997 and SLICC 2012 criteria, in the period from 1991–2016 at the Referral Centre for Paediatric and Adolescent Rheumatology Republic of Croatia, Department of Paediatrics, University Hospital Centre Zagreb and who by the end of March 2017 reached the age of majority at 18 and continued their treatment at the Department of Internal Medicine, University Hospital Centre Zagreb. Results: Out of 95 children with cSLE, 48 patients (42 females and 6 males) who attained the age of majority, were included in the study. Mean age at the time of diagnosis was 13.5 years (range 6–18), and the mean disease duration was 11 years. Mean SLEDAI-2K was 19, 25 (range 0–42) in childhood and 7125 (range 0–30) in adulthood. In adulthood, thirty-two patients (66.67%) showed improvement, three (6.25%) disease progression, six (12.5%) had the same disease activity and seven patients (14.58%) were in remission. 13 children (27%) had organ damage at the last follow up with mean SDI 0.43 (0–6) and 20 patients in adulthood (41, 67%) had organ damage with SDI 0.75 (0–6). Cataract, erosive arthritis and avascular necrosis were the most common organ damage in both groups. The most common presenting symptoms in childhood were musculoskeletal (predominantly arthritis) occurring in 34 children (70.83%), mucocutaneous (rash) noted in 31 (64.58%) and fever in 21 patients (43.75%). Of different laboratory tests the most common were positive antinuclear antibodies (ANA) screen (95.83%) and hypocomplementaemia (75%). Proteinuria was noticed in 26 children (54.17%). Similarly, in adulthood the most common symptoms were arthritis in 10 (20.83%) and rash in 8 patients (16.67%). Alopecia, headaches and visual disturbances were represented with 12.5% each. ANA screen was positive in 27 patients (56.25%) and hypocomplementaemia present in 22 patients (45.83%). Conclusions: At the time of diagnosis in childhood, disease activity is very high while in adulthood there is a significant decrease in disease activity. Higher disease activity in childhood is related to the development of the organ damage in adulthood. References: [1] Couture J, Silverman ED. Update on the pathogenesis and treatment of childhood-onset systemic lupus erythematosus. Curr Opin Rheumatol. 2016;28:488–96 [2] Brunner HI, Silverman ED, To T, et al. Risk factors for damage in childhood-onset systemic lupus erythematosus: cumulative disease activity and medication use predict disease damage. Arthritis Rheum. 2002;46:436–44 Disclosure of Interest: None declared